Investigation of doped Perovskite systems RAIO3 using density functional theory based electronic structure and thermoelectric studies. (October 2016) - Sandeep,; Rai, D. P.; Shankar, A; Ghimire, M. P.; Thapa, R. K.
Abstract: Samarium doping effects on the thermoelectric properties in Eu1-x Smx AlO3 (x=0%, 50%, and 100%) were studied using first principles calculations based thermal transport property measurement. The result indicate that the compound is an intrinsic n-type material. Samarium doping has a positive effect on the overall thermoelectric performance of the Eu1-x Smx AlO3 system, with sharp increase in figure of merit (ZT) observed when x=0, 50 and 100% up to 150K. Compared to x=0 and 100%, the case of x=50% was found to have more positive increment in ZT value suggesting that the doing to have positive effect on figure of merit in Eu1-x Smx AlO3 . Furthermore, all the samples show stable thermoelectric compatibility factors over a broad temperature range from 700 to 1000 K, which could have great benefits for their practical applications. It is concluded that the overall thermoelectric performance of the Eu1-x Smx AlO3 could be highly enhanced using doping techniques.